Fiduciaries of humanity : how international law constitutes authority - Criddle, Evan J.; Fox-Decent, Evan (New York, NY : Oxford University Press, 2016)
Over the past century, a new model of international law has developed under which a state's sovereign authority arises from the state's responsibility to respect, protect, and fulfill human rights for its people. In this work, Evan J. Criddle and Evan Fox-Decent argue that these developments mark a turning point in the international community's conception of public authority.
Previously issued in print: 2016.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on July 20, 2016).
Keywords: International law; Authority; Sovereignty; Law; International law